Prácticas de cultivo en arroz de riego en Colombia. - González Franco, Joaquín A.; Robayo P, Rafael; Ottavo F, Yecid; Ortega R, Héctor Hugo (Instituto Colombiano Agropecuario, 2018)
Arroz-Oryza sativa